Pengaruh Sistem Informasi Pengelolaan Keuangan Daerah Dan Sistem Akuntansi Keuangan Daerah Terhadap Kinerja Pemerintah Daerah : Penerapan Anggaran Berbasis Kinerja Sebagai Variabel Moderasi (Studi Emipiris Pada Pemerintah Kabupaten Maluku Tengah) - Titaley, Wilisen Josafat Alexsander; Usmany, Paul; Hariyanti, Dwi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the effect of regional financial management information systems and regional financial accounting systems on local government performance moderated by the implementation of performance-based budgeting. The sample used in this study was 47 respondents. The data analysis used in this study was Partial Least Square (PLS). The results showed that the influence of the regional financial management information system had a positive and significant influence on the performance of local governments. The results also show that the regional financial accounting system has a positive and significant influence on the performance of local governments. Furthermore, the influence of the regional financial management information system on local government performance will be weak if moderated by the implementation of performance-based budgeting. And the influence of the regional financial accounting system on the performance of local governments will be stronger if moderated by the implementation of performance-based budgeting.